2013
DOI: 10.1177/0040517513507362
|View full text |Cite
|
Sign up to set email alerts
|

New approach to assessing comfort of use of protective footwear with a textile liner and its impact on foot physiology

Abstract: We propose a new approach to assessing comfort of use of protective footwear with a textile liner. All-rubber footwear with wool liner and cotton/polyamide socks were evaluated in a study involving 30 firefighters. The study was designed to comprehensively assess comfort of use of textiles in the footwear using certain known and new research tools at the same time, that is, measurement of the microclimate inside the footwear (temperature and humidity), weight gain of the footwear, socks, and liner (weighing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…The heel and sole foot regions were highlighted as being areas of high temperature and high moisture with running thus suggesting low rates of heat and moisture transfer from the foot at these regions. Irzmanska et al (2013) similarly reported a higher inshoe temperature at the plantar region (37°C) compared to the dorsal region (36°C)…”
Section: Spatial Characteristics Of Foot and Shoe Microclimatementioning
confidence: 84%
See 3 more Smart Citations
“…The heel and sole foot regions were highlighted as being areas of high temperature and high moisture with running thus suggesting low rates of heat and moisture transfer from the foot at these regions. Irzmanska et al (2013) similarly reported a higher inshoe temperature at the plantar region (37°C) compared to the dorsal region (36°C)…”
Section: Spatial Characteristics Of Foot and Shoe Microclimatementioning
confidence: 84%
“…Consequently, heat loss from the skin to the shoe is reduced as the gradient becomes smaller (Lu et al 2013). The development of the shoe microclimate has therefore been suggested to have a decisive influence on the users sensations and perceptions of thermal comfort (Arezes et al 2013;Irzmanska et al 2013;Shimazaki and Murata 2015). The materials used within shoes and socks, the air they enclose and the air bound on the outside of the material layers are therefore important (Havenith 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative humidity inside protective footwear ranges from 96% to 100%, which increases the development of sweatdecomposing bacteria [21]. Analysing the microbiological contamination of footwear, one should always consider the presence of pathogenic bacteria and fungi.…”
Section: Evaluation Of the Protective And Functional Properties Of Bimentioning
confidence: 99%